A flexible approach on pulsed wire magnetic measurement method. (August 2022) - Ebbeni, M.; Gehlot, M.; Holz, M.; Tarawneh, H.
Abstract: The Pulsed Wire (PW) method offers a promising solution for performing local magnetic field measurements in undulators that have limited access that restricts traditional Hall-Probe (HP) measurements. With this technology, undulators can be designed with a closed frame structure, becoming more compact and cost effective. At the same time, the PW method suffers from intrinsic error sources which can impact the quality of the magnetic field measurements and therefore losing confidence in its results. This paper provides a flexible framework for calculating the magnetic field, correcting for the dispersion effect and the pulse shape. This framework is used to correct experimentally collected pulsed wire data and compare them against Hall-probe measurements for the same magnetic field. Highlights: Undulators are excellent sources of coherent X-ray sources used in research. Tuning an undulator requires high precision magnetic measurement systems. Pulsed wire method offers magnetic measurements with minimum access requirements. Dispersion and pulse effects must be compensated for magnetic field calculation. Arbitrary pulse response opens the door to accommodate novel pulse profiles.